Disability Culture Poetry: The Sound of the Bones. A Literary Essay - Kuppers, Petra (Disability Studies Quarterly, 2006)
This essay looks for myths in disability culture poetry, and uses this lens, searching for different and welcoming spaces, countries, bodies and songs, to look at two questions: what does poetry do for crip culture? And what does crip culture do for poetry? Through close readings of poems by Jim Ferris and Philip Dowd, new lands emerge, and Neil Marcus's Disabled Country comes into view. The essay frames this discussion through a poetry banquet, held as part of a disability culture course at the Institute for Medical Humanities, UTMB, Galveston, Texas.